Association of Preoperative mid-stream urine culture, Renal pelvic urine culture and Renal stone culture in the detection of Systemic inflammatory response syndrome/urosepsis post Percutaneous Nephrolithotomy - Thapa, Neeraj; Baral, Suman; Maharjan, Nabina; Chettri, Raj Kumar; Acharya, Suminma; Karki, Kamal; Mahato, Ranjit (Journal of Gandaki Medical College-Nepal, 2020)
Introduction: Urosepsis post Percutaneous Nephrolithotomy (PCNL) is a dreaded complication with high mortality rate. Objective: To find the association of preoperative midstream urine culture (PMUC), renal pelvic urine culture (RPUC) and renal stone culture (RSC) in the post-operative development of Systemic Inflammatory Response Syndrome (SIRS) and urosepsis. Methods: It was a prospective cross-sectional observational study. The study included all symptomatic patients meeting the inclusion criteria who underwent Percutaneous Nephrolithotomy from 18th August, 2019 to 28th March, 2020. PMUC, RPUC and RSC were done and analyzed accordingly. Results: A total of 140 (73 males, 67 females) patients underwent PCNL. PMUC was positive in 15% (21/140) as compared to RPUC and RSC which were 7.9 % (11/140) and 4.3% (6/140) of total cases. None of the patients had simultaneous culture positivity in all the three types of specimens. Only two (1.42%) patients had simultaneous positivity in pelvic urine culture and stone culture. The organisms obtained in pelvic urine culture and stone culture were same i.e. Klebsiella and Escherichia coli respectively. Only two (1.42%) patients developed SIRS post PCNL, where in both the cases stone culture were positive but PMUC and RPUC were negative. Urosepsis was found in none of the patients. In the Fischer Exact test PMUC and RPUC were not statistically significant in the detection of SIRS post PCNL. Whereas only RSC showed statistical significance in the detection of SIRS. Conclusion: Stone culture has high prediction for SIRS and it might be considered for patients undergoing PCNL in order to prevent stone related infective complications.